Løgstrup’s Criticism of Kierkegaard - Epistemological and Anthropological Dimensions - Karlsen, Gunnar M. (KIERKEGAARDIANA, 1994)
Løgstrup’s Criticism of Kierkegaard - Epistemological and Anthropological Dimensions